A theorical point of view of reality, perception, and language. Issue 1 (2nd January 2014) - Nescolarde‐Selva, Josué Antonio; Usó‐Doménech, Josep‐Lluis; Gash, Hugh
<x xml:space="preserve">Abstract</x> It is possible to view the relations between mathematics and natural language from different aspects. This relation between mathematics and language is not based on just one aspect. In this article, the authors address the role of the Subject facing Reality through language. Perception is defined and a mathematical theory of the perceptual field is proposed. The distinction between purely expressive language and purely informative language is considered false, because the subject is expressed in the communication of a message, and conversely, in purely expressive language, as in an exclamation, there is some information. To study the relation between language and reality, the function of ostensibility is defined and propositions are divided into ostensives and estimatives. © 2013 Wiley Periodicals, Inc. Complexity 20: 27–37, 2014